Preparation, In-vitro, and Ex-vivo Evaluation of Ondansetron Loaded Invasomes for Transdermal Delivery - Omar Saeb Salih; Entidhar J. Al-Akkam (College of Pharmacy University of Baghdad, 2023)
Invasomes are newly developed types of nanovesicles. A vesicular drug delivery system is considered one of the approaches for transdermal delivery to enhance permeation and improve drug bioavailability. Ondansetron is a serotonin receptor antagonist used for treating vomiting associated with different clinical cases. The study aimed to prepare invasomal dispersions for improving permeation of ondansetron across the skin with a controlled release pattern. Twenty-seven formulas of ondansetron-loaded invasomes were prepared by a modified mechanical dispersion method. These formulas were optimized by studying the effect of variables on entrapment efficiency. Vesicle size, polydispersity, zeta potential, in-vitro release and ex-vivo permeation studies were done for the optimized formulas. The selected formula was )F25( had )88.24%±0.04 (entrapment, (317.7 nm) vesicle size, (0.29) polydispersity, and (-31.5mV) zeta potential. In-vitro release study showed That (F25) had 75% release after (12) hrs., and dissolution followed the Korsmeyer-Peppas model with anomalous diffusion. Ex-vivo permeation study showed steady-state flux was 340.2 µg/cm2.hr with no lag time using rat skin tissue. A transmission electron microscope was done to visualize the selected formula. Invasomes are considered promising drug delivery systems for transdermal delivery of ondansetron, ensuring efficient permeation with a sustained release pattern.